KETERLAKSANAAN DAN RESPONS SISWA TERHADAP PENERAPAN GUIDED INQUIRY BERBANTUAN LKPD BERORIENTASI SOCIO-SCIENTIFIC ISSUES - Hidayat, Amelia Tsabitah; Hidayati, Siti Nurul (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This study aimed to describe the implementation and student responses to the application of guided inquiry assisted by worksheets oriented to Socio-Scientific Issues (SSI). The type of research used is descriptive quantitative with pre-experimental design. The subjects in this study were 32 students of class VIII. The instruments used to collect data were learning implementation sheets and student response questionnaires. The technique of collecting data in this research is using observation and survey methods. The results of the study showed that learning was carried out very well in the two meetings and the students' responses to the learning model received very good responses as shown by an average result of ? 76%.